Treatment of ureteropelvic junction obstruction and urolithiasis in children with minimally invasive surgery. Issue 2 (May 2022) - Masieri, Lorenzo; Sforza, Simone; Manera, Alekseja; Lambertini, Luca; Crisci, Alfonso; Cini, Chiara; Mantovani, Alberto; Cocci, Andrea; Minervini, Andrea; Carini, Marco
Background: Ureteropelvic Junction Obstruction (UPJO) is the most common congenital ureteral anomaly. Nowadays, according to the increasing incidence of urolithiasis, 20% of children with UPJO presents urolithiasis. Open pyeloplasty was the standard treatment before the introduction of minimally invasive surgery (MIS). Nevertheless, only scattered experiences on MIS were previously described and universal agreement on the treatment of UPJO plus urolithiasis is still missing. Objective: The study aim was to describe our experience with a series of pediatric patients affected by UPJO and urolithiasis treated with robot-assisted pyeloplasty (RAP) and endoscopic removal of stones using a flexible cystoscope and a stones basket in a singular tertiary referral center. Material and methods: We retrospectively reviewed our data from pediatric patients affected by UPJO and urolithiasis undergoing RAP between April 2013 and December 2019. The analysis was conducted on seven patients. All procedures were performed by one expert robotic surgeon and one endoscopic surgeon skilled in the management of urolithiasis. Results: The mean age was 7 years (IQR 4–16). The median stone area was 77.7 mm two (IQR 50.2–148.4). Most of them (71.4%) presented preoperative symptoms. The median operative time was 110 min (IQR 104–125) with a console time of 90 (IQR 90–105). The median length of stay was 5 days (IQR 4–5). Median follow-up was 16 months (IQR 10–25). Conclusion: RAP with concomitant flexible ureteroscope is a safe and effective option for the simultaneous management of UPJO with urolithiasis with excellent outcomes in children.